Technology in Arabic Language Learning - Faidatul Baroro (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2025)
This study explores the crucial role of technology in learning the Arabic language, emphasizing its importance in today's digital landscape and the challenges faced during its implementation. In this context,